Hemangioma capilar congênito em um bezerro girolando - Guimarães, João Gustavo Pessoto; Souza, Freddi Bardela [UNESP]; Petrillo, Vitor Hugo Mion; Oliveira, Andreza Pimenta de [UNESP]; Nogueira, Gustavo Milhomens; Oliveira Filho, José Paes de [UNESP] (My University, 2010)
Hemangioma is a benign neoplasia of endothelial cells resultant by vascular mal formations and disorganized proliferation. In this report shows clinical and histological findings of a case of hemangioma in Girolanda calf from Pardinho, São Paulo. Histolgical examination of the biopsy excisional shown findings suggestive of the congenital capillary hemangioma.

Hemangioma é uma neoplasia benigna de células endoteliais resultante de má formações vasculares e proliferação desorganizada de elementos vasculares. Este relato descreve os achados clínicos e histológicos de um caso de hemangioma em um bezerro Girolando de uma fazenda em Pardinho - São Paulo. O exame histológico da biópsia excisional revelou achados sugestivos de hemangioma capilar congênito.
Congenital capillary hemangioma in Girolando calf
Keywords: Neoplasia; Congenital capillary hemangioma; Calf; Neoplasia; Hemangioma capilar congênito; Calf